Bonus Ratio, Individual Performance, and Self-Selection of Housing Brokerage Employees - Yu, Cheng; Lee, Zong-Sheng; Wang, Zhi-Yu; Lee, Chun-Chang; Lin, Chueh-Shih (Asian Journal of Empirical Research, 2017)
This study explored the Self-selection issues present in the individual bonus ratio and individual performance of housing brokerage employees. The participants in the survey were housing brokerage employees in Kaohsiung City, Taiwan. In this study, individual performance and individual bonus ratio were designated as interacting endogenous variables. Evaluations were conducted using two-phase simultaneous equations. The empirical results showed the following: 1. a higher bonus ratio resulted in better individual performance, while better individual performance resulted in a higher bonus ratio. 2. Male workers performed significantly poorer than female workers. 3. Junior college education, hours of work, and low salary had a significant positive effect on individual performance. 4. Significantly more men than women selected brokerage work with a high individual bonus ratio. 5. Employees with university or higher education, low salary, and working in the direct selling system had significantly lower individual bonus ratios.